Channel‐lobe transition zone development in tectonically active settings: Implications for hybrid bed development. (22nd March 2022) - Brooks, Hannah L.; Ito, Makoto; Zuchuat, Valentin; Peakall, Jeff; Hodgson, David M.
Abstract: Channel‐lobe transition zones are dynamic areas located between deepwater channels and lobes. Presented here is a rare example of an exhumed channel‐lobe transition zone from an active‐margin setting, in the Kazusa forearc Basin, Boso Peninsula, Japan. This Plio‐Pleistocene outcrop exposes a thick (tens of metres) channel‐lobe transition zone succession with excellent dating control, in contrast to existing poorly dated studies of thinner (metres) deposits in tectonically quiescent settings. This high‐resolution outcrop permits the roles of climate and associated relative sea‐level changes on stratigraphic architecture to be assessed. Three development stages are recognised with an overall coarsening‐upward then fining‐upwards trend. Each stage is interpreted to record one obliquity‐driven glacioeustatic sea‐level fall‐then‐rise cycle, based on comparison with published data. Deposition of the thickest and coarsest strata, Stage 2, is interpreted to record the end of a period of relative sea‐level fall. The thinner and finer strata of Stages 1 and 3 formed during interglacial periods where the stronger Kuroshio Oceanic Current, coupled to increased monsoonally driven tropical cyclone frequency and intensity, likely resulted in inhibited downslope sediment transfer. A key aspect of channel‐lobe transition zone deposits in this case is the presence of a diverse range of hybrid beds, in contrast to previous work where they have primarily been associated with lobe fringes. Here hybrid bed characteristics, and grain‐size variations, are used to assess the relative importance of longitudinal and vertical segregation processes, and compared to existing models. Compared to channel‐lobe transition zones in tectonically quiescent basin‐fills, this channel‐lobe transition zone shows less evidence of bypassing flows (i.e. thicker stratigraphy, more isolated scour‐fills, fewer bypass lags) and has significantly more hybrid beds. These features may be common in active basin channel‐lobe transition zones due to: high subsidence rates; high sedimentation rates; and disequilibrium of tectonically active slopes. This disequilibrium could rejuvenate erodible mud‐rich substrate, leading to mud‐rich flows arriving at the channel‐lobe transition zone, and decelerating rapidly, forming hybrid beds. Abstract : Utilising exceptional outcrops of a Pleistocene channel‐lobe transition zone in Chiba, Japan, this study investigates the evolution of this enigmatic zone in a tectonically active slope setting. Well constrained age dating of ash layers from previous studies indictes that deposits in the outcrop studied span 30 kyr, allowing high resolution comparison to sea‐level and climate changes in the region. Compared to other outcrop models from inactive tectonic settings, this outcrop consists of thicker stratigraphy; more isolated and smaller scours; fewer bypass lags; more grain‐size breaks; and most notably a particularly high abundance and vareity of hybrid beds (combined turbidites and debrites).